Métodos de tratamentos na semente de tremoço (Lupinus albus) para elaboração de farinha: propriedades nutricionais, tecnofuncionais e aplicação em massas alimentícias frescas - Pontes, Claudilane Martins (2024)
Lupine (Lupinus albus) is a nutritious legume appreciated for its high protein content, and its consumption has been associated with a series of beneficial health effects. Despite this, inclusion in the diet is still low, and this can be attributed to issues such as difficulty in preparation, digestibility and sensory problems. Currently, the treatments used in the preparation of lupine consist of methods that require a long processing time, generating a reduction in nutritional quality. Flour is an excellent product for the cultivation of lupine for consumption and a protein vehicle for the enrichment of pasta produced with weak flours. Therefore, the objective of this study was to investigate methods of treating lupine for the preparation of flour, namely: germination, pretreatment, thermal and non-thermal treatment; isolated and combined; in addition, to verify the influence of the addition of flour in the percentages of 10% (M10), 20% (M20) and 30% (M30) in the production of fresh pasta. The nutritional, technofunctional and bioactive properties of lupin flour were evaluated and the fresh pastas were tested for their microstructure (SEM), physicochemical, texture profile (APT), cooking quality (NMR) and accessible sensory characteristics. The results showed that the flours obtained from the germinated grain and those obtained by maceration and combined with microwave heat provided improvements in nutritional properties, maintaining high protein and bioactive compound content. On the other hand, maceration and conventionally combined with heat under pressure in the seed induced an improvement in the leaching of compounds into the cooking water, producing flours with lower protein and bioactive content. However, it is worth mentioning that they resulted in intense protein denaturation, improving the technological properties of the flour such as water absorption, solubility and swelling power. An SEM analysis of the pastas showed that the lupin flour changed the microstructure compared to the control, with a more compact structure and discontinuity of the starch and protein matrix. The doughs with a higher proportion of lupin flour (M20 and M30) presented a more yellowish coloration influenced by the higher protein content. The firmness of the doughs increased for M10 and M20 due to a greater presence of proteins and more organized microstructure, however, in the dough occupied by M30 there was a reduction influenced by the disorganization of the structure and loss of solids (CL). The NMR of the dough control identified a higher intensity of glycosidic bond peaks of α-1,4 and α-1,6 in the cooking water. A sensory analysis indicated that the doughs M10 and M20 were accepted by the tasters, while M30 presented smaller resources due to changes in texture and flavor. The results of this study provided important information on how the pretreatments used together with thermal treatments, isolated or combined, can modify the properties of the flour, generating a direct impact on the characteristics of the final product. The addition of lupin flour to fresh pasta improved its nutritional and technological properties without compromising sensory accessibility. In industrial terms, this could represent an alternative ingredient for artisanal pasta, allowing diversification and low-cost production.